Caffeine supplementation: Ergogenic in both high and low caffeine responders - Apostolidis, A.; Mougios, V.; Smilios, I.; Rodosthenous, J.; Hadjicharalambous, M. (International Journal of Sports Physiology and Performance, 2019)
Purpose: Inconsistent results among studies examining the effects of caffeine on exercise performance are potentially due to interindividual variability in biological responses to caffeine ingestion. The aims, therefore, of the present study were to identify high and low caffeine responders and compare the influence of caffeine on exercise performance and biological responses between groups during a simulated soccer-game protocol on treadmill. Methods: Well-trained soccer players were distinguished as high (n = 11) and low (n = 9) caffeine responders based on resting blood pressure, plasma glycerol, nonesterified fatty acid, and epinephrine responses to caffeine. Participants underwent 2 simulated soccer-game protocols on a treadmill after caffeine (6 mg/kg) or placebo ingestion. Exercise performance and several biological responses were evaluated. Results: Exercise performance did not differ between the high and low responders to caffeine (P > .05). However, time to fatigue (high, caffeine: 797 [201] s vs placebo: 487 [258] s; low, caffeine: 625 [357] s vs placebo 447 [198] s) and countermovement jump (high, caffeine: 42.1 [5.5] cm vs placebo: 40.5 [5.7] cm; low, caffeine: 41.0 [3.8] cm vs placebo: 38.8 [4.6] cm) improved with caffeine relative to placebo (P < .001). Rating of perceived exertion was lower (P < .001) in high (13.4 [2.3]) than in low responders (14.3 [2.4]) with caffeine ingestion. Conclusions: Caffeine improved aerobic endurance and neuromuscular performance in well-trained soccer players regardless of their responsiveness to caffeine at rest. Since no changes in substrate utilization were found with caffeine supplementation, performance improvements could be attributed to positive effects on the central nervous system and/or neuromuscular function, although the precise mechanism remains unclear.